2012
DOI: 10.1039/c2cs35034c
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic alkynylation: the dark side of acetylene chemistry

Abstract: In addition to the well-established nucleophilic alkynylation, the use of electrophilic alkynes can expand 5 tremendously the scope of acetylene transfer reactions. The use of metal catalysis has recently led to a rebirth of this research area. Halogenoalkynes, hypervalent alkynyliodoniums, acetylene sulfones and in situ oxidation of terminal acetylenes are the most often used for electrophilic alkynylation. Heteroatoms such as N, O, S and P can be now efficiently alkynylated. For C-C bond formation, electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
165
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 401 publications
(170 citation statements)
references
References 90 publications
0
165
0
5
Order By: Relevance
“…The reaction was faster with electron-deficient reagent 1c, however. Methylated TIPS-EBX reagents 1e and 1f led to the formation of the ethynylated product 3b in moderate yields and relatively short reaction times (entries [4][5]. Finally, we found that TIPS benziodioxole reagents 5 and 6 are also efficient alkynylation reagents under these conditions, although in this case the alkynylation reaction is slower (entries 6-7).…”
Section: Alkynylation Reactions With Modified Ethynyl Benziodoxolonesmentioning
confidence: 76%
See 3 more Smart Citations
“…The reaction was faster with electron-deficient reagent 1c, however. Methylated TIPS-EBX reagents 1e and 1f led to the formation of the ethynylated product 3b in moderate yields and relatively short reaction times (entries [4][5]. Finally, we found that TIPS benziodioxole reagents 5 and 6 are also efficient alkynylation reagents under these conditions, although in this case the alkynylation reaction is slower (entries 6-7).…”
Section: Alkynylation Reactions With Modified Ethynyl Benziodoxolonesmentioning
confidence: 76%
“…The characterization data corresponded to the reported values. [4] 2-Iodosyl-5-nitrobenzoic acid and 2-iodosyl-3-nitrobenzoic acid (19,20) Following a reported procedure, [5] fuming nitric acid (3.3 mL) was added to 2-iodobenzoic acid (14) (5.0 g, 20 mmol, 1.0 equiv) in concentrated H2SO4 (6.7 mL). The reaction was equipped with a cooler and a nitrous vapor trap and was heated at 100 °C for 1 h. The reaction mixture was then poured onto ice-water and filtered.…”
Section: -[(Triiso-propylsilyl)ethynyl]-12-benziodoxol-3(1h)-one (1b)mentioning
confidence: 99%
See 2 more Smart Citations
“…In stark contrast, the addition of alkynes onto nucleophiles requires an inversion of their inherent reactivity (an Umpolung, Scheme 2.1, B). This approach is more challenging and has been consequently less developed [7][8][9]. When considering the omnipresence of nucleophiles not only in synthetic organic chemistry, but also in chemical biology and materials science, this is an important shortcoming.…”
Section: Introduction: the Umpolung Of Alkynesmentioning
confidence: 99%